Budaya Ngaji Kitab Kuning di Pondok Pesantren Salaf Nurul Muhibin Kemuja Bangka Provinsi Kep. Bangka Belitung - Subri, Subri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2016)
Islamic boarding school has at least three main roles, namely as an Islamic educational institutions, Islamic preaching board and as a community development agency. As an Islamic educational institutions, boarding school until today has undergone a good development of the education system, curriculum, learning, teaching patterns even to the subject matter presented. Whereas the basic essence of the boarding school will never be separated from the elements of the boarding school itself, mosques, religious scholars, students and the teaching of classical texts (yellow book). In fact, Salaf boarding school Nurul Muhibbin which is located in the Kemuja village Bangka district that still exist bequeath concepts and traditional culture methods yellow book (the Koran) as the main material being taught to the students.Given this reality, then this article is focused on the culture of reading the Koran in the yellow book Salaf boarding school, Nurul Muhibbin Kemuja Bangka. The purpose of the research is to find out how the culture and implementation of the Koran of Yellow Book at Salaf boarding school, Nurul Muhibbin Kemuja Bangka.The result of the research shows that the culture of reading the yellow book of Koran at salaf boarding school Nurul Muhibbin Kemuja Bangka is still using traditional methods which are called sorogan and bandongan. There are other methods used in the implementation of yellow book of Koran done by the students together with senior students under the supervision of the preachers which is called mudzakaroh method. This method is used to repeat, analyze and discuss the book materials that have been taught. Besides that method, that the institution is also implementing classical learning, scheduled and graded. The point is that the students learn in class in a permanent building with facilities bench learning, whiteboard, markers and the teacher's desk with class schedule that has been attached, the 7-year study period for male students and four years for female students. While the material taught is classical Islamic books which is reading Arabic without harakat and yellow paper as the main characteristic . There are some constraints faced by this institution. They are limited human resources among their major, students with minimal background knowledge of the religion, the heterogeneity of the graduate students and the lack of discipline of teachers such as not coming to the class on time.